RESEARCH ON DAMAGE ZONE IN STRESS FIELD INTENSITY METHOD - MA ZhiQuan; TANG DongLin (Jixie qiangdu)
In view of the controversial problem of damage zone in stress field intensity method,a method was proposed to determine damage zone by stress contour. Stress contour calculating steps were given. The example was given to demonstrate the calculating process. The result of the example analysis shows that the damage zone is not a regular and spherical zone,but is irregular. The method can reflect the real damage zone and is accord with the fatigue mechanism. The damage zone size and the load applied show a quadratic curve relationship and monotone increase. This method considers the changing load’s effect on the damage zone and even large load is applied it still can accurately predict the fatigue life of components. In order to prove the universality of the method,two examples with different notch shapes and load forms were given to verify. The result shows that the method can accurately predict the fatigue life of components with any notch shape and any load form and good predicted results have been achieved.